Influence of Clusters on the Intensity of Innovation Outputs - Miroslav Žižka; Petra Rydvalová (Amfiteatru Economic Journal, 2014)
The article evaluates the impact of clusters on innovation outputs in the regions of the Czech Republic. The research was divided into four main phases. An overview of all institutionalised clusters in the Czech Republic, including innate clusters, was compiled in the first phase. Location quotients were used to identify innate clusters. For institutionalised clusters the main declared field specialisation, membership basis and cluster age were established. In the second phase, 5 most important branches were defined per each region by number of employees. Subsequently, the hypotheses that innovation characteristics of the regions depend on the number of clusters, their average age and the number of members were tested. Innovations were characterised by patent applications, utility models, total R&D expenditure and export of technology services. All values were examined as incremental for the period of 2009 to 2012 per one full-time researcher. None of the determined hypotheses were confirmed. There is no systematic dependence between the innovation outputs in the regions and clusters. The possible reasons for this fact are discussed in the article, such as the short time clusters have been operating in the CR, the impact of the economic crisis or underestimating the existence of innate clusters. In the last phase of the research, innovation outputs were evaluated for the branches with operating clusters in respective regions and compared with total innovations per branch in the CR. Two regions were selected to serve as an example. The analysis showed that innate non-institutionalised clusters can also have a major impact on innovation outputs in regions.
Keywords: D85; L14; L24; O31; O32; 330; branch structure; cluster; cluster initiative; innovation; innovation outputs; institutionalized cluster; Porterian cluster